Responses to indirect complaints as restricted activities in Therapeutic Community meetings - Pino, Marco (John Benjamins, 2015)
In this chapter I investigate how the staff members of a mental health Therapeutic Community in Italy avoid displays of affiliation in response to residents’ indirect (or third party) complaints. I show how this restriction can be embodied in different practices: ignoring a resident’s turn carrying a possible complaint, avoiding attending the complaint-components of a resident’s turn, and disaffiliating with a resident’s complaint. I also discuss a deviant case in which affiliation is produced and is later treated by the staff members as a problematic stance to be produced following a resident’s complaint. I argue that through a restriction on affiliation the staff members implement the institutionally-relevant identity of intermediaries, whose task is to encourage the residents’ compliance to the decisions of absent third parties.